Bond strength of GiR in cross-laminated timber: A preliminary study. (27th September 2021) - Sofi, M.; Lumantarna, E.; Hoult, Ryan; Mooney, Michael; Mason, Nicholas; Lu, Jinghan
Highlights: Glued-in rods (GiR) as moment connections in cross laminated timber (CLT) is investigated. The influence of the embedment length of GiR and the CLT arrangement is reported. Design recommendation are made for GiR connections in CLT. Abstract: The popularity of cross-laminated timber (CLT) has increased significantly over recent years, with numerous low- to mid-rise buildings being constructed with CLT panels as the load-bearing structural system. Glued-in rods (GiR) have been used in the construction and retrofitting of timber structures and recently found its use in CLT elements. Embedded into the timber with structural grade adhesives, GiR enable stiff connections between timber and other structural members. Due to the complex force mechanisms occurring within these joints, there is yet to be consensus on a suitable method to predict their pull-out strength or failure mechanism. There is lack of experimental research on performance of GiR embedded into CLT. This paper examines previous research on glued-in rod connections as typically applied to solid timber and other engineered timber products. It aims to identify the factors contributing to the strength and failure modes of this connection, as well as the current models that are used for the analysis and design of glued-in rods. A series of 30 experiments were undertaken to investigate the load carrying capacity of single GiR bonded into CLT panels to identify the influence of (i) the bonded length of rod; and, (ii) the direction of the middle ply of the CLT panel on these results. The experimental results indicate that the pull-out strength is largely dictated by the embedment length.